Effect of Capital, Earning, and Liquidity on Audit Opinions Going Concern (Empirical Study on Islamic Commercial Banks Registered with the Financial Services Authority (OJK) 2017-2020 Period) - Latif Azizah; Sutarti; Kristanti Rahman (Urecol Journal. Part B: Economics and Business, 2021)
Effect of Capital, Earning, and Liquidity on Audit Opinions Going Concern (Empirical Study on Islamic Commercial Banks Registered with the Financial Services Authority (OJK) 2017-2020 Period). This study aims to determine the Effect of Capital, Earning, and Liquidity on Audit Opinions Going Concern (Empirical Study on Islamic Commercial Banks Registered with the Financial Services Authority (OJK) for the 2017-2020 period). The population of this study is Islamic Commercial Banks Registered with the Financial Services Authority (OJK) for the 2017-2020 period. The sampling technique used is purposive sampling, the type of data used is secondary data and 9 Islamic Commercial Banks are used as samples. Statistical analysis in this study used multiple linear regression. The results of this study indicate that: Capital has an effect on Audit Opinion Going Concern. Earnings affect the Audit Opinion Going concern. Liquidity has no effect on Audit Opinion Going Concern. Capital, Earning, Liquidity simultaneously affect theAudit Opinion Going Concern.